Investigation of antifungal, antibiofilm and anti-filamentation activities of biocides against Candida isolates - Ozturk, Ali; Abdulmajed, Olkar; Aydin, Merve (Annals of Medical Research, 2021)
Aim: This study was aimed to evaluate the antifungal, antibiofilm, and anti-filamentation activities of three commonly used biocides against clinical Candida isolates.Material and Methods: The in vitro activities of benzalkonium chloride (BZC), chlorhexidine digluconate (CHX), and triclosan (TRC) were studied against three Candida (C. albicans, C. parapsilosis, and C. glabrata) isolates. The isolates were identified, using the germ tube test, Cornmeal agar, and ID32 C (bioMerieux, France) kit. Antifungal susceptibility of these isolates was determined using the broth microdilution method. Antibiofilm activity of biocides were assessed with a colorimetric method based on crystal violet. The effect of biocides on the ability of C. albicans to form hyphae was examined microscopically.Results: The antifungal, antibiofilm, and anti-filamentation activities of biocides used were determined against Candida isolates. Antifungal activities of biocides against Candida isolates ranged from 1–4 µg/ml. The potent fungistatic effect of biocides tested was detected against Candida spp. at 1 µg/ml. All tested biocides showed good antifungal activity against Candida isolates. The results of the antibiofilm activity assay showed that the highest biofilm inhibition ratios were reported in BZC, CHX, and TRC (66%, 60.3%, and 58%, respectively) at 16 and 32 µg/ml. The lowest biofilm inhibition ratios were reported at MIC values for each biocide between 6% and 12%. In addition, the anti-filamentation activity of biocides tested was screened against C. albicans at concentrations of 1, 2, and 4 µg/ml of biocide and the inhibition rates varied from 10% to 59%.Conclusions: Important information has been obtained about the fungistatic/fungicidal, antibiofilm activities, and effects on C. albicans micromorphology of the biocides used in this study.
Keywords: Antifungal; antibiofilm; anti-filamentation; biocides; emcandida /em